Linear reinforcement learning in planning, grid fields, and cognitive control - Payam Piray (Nature Portfolio, 2021)
Models of decision making have so far been unable to account for how humans’ choices can be flexible yet efficient. Here the authors present a linear reinforcement learning model which explains both flexibility, and rare limitations such as habits, as arising from efficient approximate computation